Effect of KOH concentration in the gel polymer electrolyte for direct borohydride fuel cell - Ng, P.L.; Mohamad, A.A.; Ahmad, Z.A.; Basirun, Wan Jefrey; Alias, Y.; Jamaludin, A. (Wiley, 2012)
The performance of a direct borohydride fuel cell (DBFC) based on a polyacrylamide (PAAm) gel polymer electrolyte system is investigated at different electrolyte concentrations. The DBFC, constructed using 2M sodium borohydride (NaBH4) as the fuel and potassium hydroxide (KOH) solution gelled with PAAm as the electrolytes yield the highest electrical conductivity of 2.73 x 10-1 S cm-1 at 6M KOH. The optimized composition, PAAm + 2M NaBH4 + 6M KOH, and the selected composition, PAAm + 2M NaBH4 + 3M KOH are then used in preparing the cells. Open-circuit voltages for fuel cells is about 0.85-0.92 V, and the discharge characteristic produce discharge capacities of about 257.12-273.12 mAh cm-2 for cells with PAAm-6M KOH. Current-voltage and current density-power density plots and internal resistance for both cells are almost the same. (c) 2011 Wiley Periodicals, Inc. J Appl Polym Sci, 2012